Subject Performance in Two Six-Man Communication Network Experiments - Marshall, Wayne S. (Management Science, 1966)
A detailed report of subjects' behavior in two six-man communication network experiments is given. These are perhaps the first six-man experiments in the Bavelas-type communication networks to be reported. Main features of subject performance lead one to question the idea of “optimal organizational behavior” even in this very simple situation.